PEER RISK AND PROTECTIVE FACTORS IN ADOLESCENCE: IMPLICATIONS FOR DRUG USE PREVENTION - Goliath, Veonna; Pretorius, Blanche (Social Work/Maatskaplike Werk, 2016)
Evidence-based practice guidelines for drug use prevention with adolescents propose focusing on increasing protective factors and reducing risk factors associated with drug use. The present article reports on a qualitative study undertaken with 10 adolescent drug users and 29 non-users from a historically marginalised community in Port Elizabeth, South Africa. The findings reveal peer risk and protective factors associated with drug use, and offer recommendations for how protective factors can be increased and peer risk factors mobilised as protective mechanisms and sources for promoting resilience in drug use prevention among adolescents.